Problemes de fraseologia i fraseografia catalanes - Morvay, Károly (Caplletra. Revista Internacional de Filologia, 1995)
The goal of this paper is to analyze the treatment of phraseological units (idioms) in current Catalan lexicography, including bilingual dictionaries (Catalan / Italian, German, Portuguese, etc.) and focusing on questions of Catalan-Hungarian lexicographical work.